2015
DOI: 10.1136/annrheumdis-2015-eular.3662
|View full text |Cite
|
Sign up to set email alerts
|

AB1097 The Impact of Systemic Lupus Erythematosus on Work Productivity: Data from Patients from the Province of Cordoba, Argentina

Abstract: BackgroundSince SLE tends to occur during the productive years of life, the cost of the disease derives not only from direct health expenditures but also from the impact the disease has on work productivity.ObjectivesTo describe the impact of SLE on work productivity and to assess the factors influencing this outcome measure.MethodsWe studied 225 patients (1987 ACR criteria), age ≥16 years. Work productivity was assessed with the WPAI:Specific Health Problem for SLE. The WPAI yeilds four scores: % work time mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our study also showed that both work and non-work related productivity impairments were significantly associated with poor QoL measured with SF-36. This finding concurred with the SLE cohort in Argentina 32 and rheumatoid arthritis populations. 41,42 However, due to the crosssectional nature of this study, a causal relationship of poor QoL and work productivity could not be ascertained.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study also showed that both work and non-work related productivity impairments were significantly associated with poor QoL measured with SF-36. This finding concurred with the SLE cohort in Argentina 32 and rheumatoid arthritis populations. 41,42 However, due to the crosssectional nature of this study, a causal relationship of poor QoL and work productivity could not be ascertained.…”
Section: Discussionsupporting
confidence: 90%
“…Systemic lupus erythematosus mainly affects young females during the career-building phase of life. Therefore, burden of the disease towards patients' work productivity 11,16,18,19,32 and QoL 6 is substantial. Despite the fact that the Asian population displays more severe SLE, 33 there is still a relative paucity of studies quantifying the socio-economic burden of the disease which may indirectly influence patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation